2021
DOI: 10.1002/cre2.427
|View full text |Cite
|
Sign up to set email alerts
|

Prevalance and clinical characteristics of gingival recession in Greek young adults: A cross‐sectional study

Abstract: Objective: The current cross-sectional study aimed to investigate the prevalence of gingival recession (REC) in a sample of young individuals. In addition, the association with several risk factors was examined.Materials & methods: A 104 subjects, aged 18-30 years old, were randomly enrolled in the study. Participants were requested to fill in a simple structured questionnaire in order to provide information on dental hygiene habits, educational level, smoking and history of orthodontic treatment. Afterwards, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
2
3
0
1
Order By: Relevance
“…This finding supports the widely held belief that a sufficient width of keratinized gingiva is critical in preventing gingival recession at a specific site. Similar findings were observed by Mamta Singh et al This study showed thin gingival biotype more when compared to thick gingival biotype (41). In another previously done research, the thin gingival biotype was found to be 43.25 percent prevalent, while the thick gingival biotype was found to be 56.75 percent prevalent whereas in our study it was 43.39% of thick and 56.6% of thin gingival biotype (42).…”
Section: Resultssupporting
confidence: 90%
“…This finding supports the widely held belief that a sufficient width of keratinized gingiva is critical in preventing gingival recession at a specific site. Similar findings were observed by Mamta Singh et al This study showed thin gingival biotype more when compared to thick gingival biotype (41). In another previously done research, the thin gingival biotype was found to be 43.25 percent prevalent, while the thick gingival biotype was found to be 56.75 percent prevalent whereas in our study it was 43.39% of thick and 56.6% of thin gingival biotype (42).…”
Section: Resultssupporting
confidence: 90%
“…Nevertheless, in our work, no association was demonstrated between gender and the presence of GRs. These findings are in agreement with the data by Fragkioudakis el al ( Fragkioudakis et al, 2021 ) that reported no statistical difference between females and males in a young patients sample. Data from our work showed a statistically significant positive association between age and the presence of GRs.…”
Section: Discussionsupporting
confidence: 94%
“…However, other surveys showed a higher prevalence in the upper premolar and molar area ( Serino et al, 1994 , Röthlisberger et al, 2007 , Slutzkey and Levin, 2008 , Vignoletti et al, 2020 ). Fragkioudakis et al ( Fragkioudakis et al, 2021 ) showed that lower left canines and left fist premolars were the most affected teeth by GRs.…”
Section: Discussionmentioning
confidence: 99%
“…Although CAL on the direct buccal and lingual may be due to gingival recession, we included these measurements in the data analysis since periodontal inflammation, a focus of our study, is one of the primary factors contributing to gingival recession. [62][63][64][65][66] Moreover, two other approaches were utilized, [67][68][69][70] which included the increase in number of teeth with PPD ⩾ 4 mm and BOP on the same tooth, 67 or increase in number of teeth with CAL ⩾ 3 mm and PPD ⩾ 4 mm at the same site 68 to assess the associations. The periodontal parameter of 'having a site with CAL ⩾ 3 mm and PPD ⩾ 4 mm at the same site' would help to reduce, at least partially, the potential confounding of gingival journals.sagepub.com/home/taj TherapeuTic advances in chronic disease recession at the buccal and lingual sites, although that would create a new bias with missing of sites with CAL but no pocket depth at the interproximal areas.…”
Section: Discussionmentioning
confidence: 99%